GUIDELINES FOR THE LEARNING RESOURCE MANAGEMENT OF EDUCATIONAL INSTITUTIONS UNDER THE OFFICE OF PHRA NAKHON SI AYUTTHAYA SECONDARY EDUCATIONAL SERVICE AREA - Imudom , Wariya; Bunchai , Prayoon; Rupan , Phonthep (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aims to 1) study the conditions and problems of learning resource management of educational institutions. Under the jurisdiction of the Phra Nakhon Si Ayutthaya Secondary Educational Service Area Office and 2) present guidelines for managing learning resources of educational institutions. Under the jurisdiction of the Phra Nakhon Si Ayutthaya Secondary Educational Service Area Office The population used in the research in step 1 is the director of the secondary educational institution educational institution director Head of Academic Administration Building supervisor or media development supervisor Technology and learning innovation, 29 locations, 4 people each, totaling 120 people. The tools used in the research include 1 research questionnaire. Statistics used in the research include frequency values, percentages, averages, and deviation Standard: The population used in the research, step 2, includes 4 educational institution administrators and 3 educational administration academics, which were obtained by means of specific selection. The tools used in the research included an interview form. The researcher collected data from the informant himself. The research results found that; 1) Current administrative conditions Manage learning resources of educational institutions under the Phra Nakhon Si Ayutthaya Secondary Educational Service Area Office. Overall, there is a high level of practice. When considering each aspect, it was found that the area with the highest average was the management of learning resources in the community, followed by the management of digital learning resources. As for the management of learning resources in educational institutions are the lowest ranked. As for the problem of management of learning resources of educational institutions under the Phra Nakhon Si Ayutthaya Secondary Educational Service Area Office. Overall, there is a low level of practice. When considering each aspect, it was found that the aspect with the highest average was the management of digital learning resources, followed by the management of learning resources in the community, as for the management of learning resources in is the lowest ranking, respectively 2) Guidelines for developing and managing learning resources of educational institutions under the Phra Nakhon Si Ayutthaya Secondary Educational Service Area Office found that there should be operations divided according to all 3 elements.